STUDI PERSEBARAN TIPE AIRTANAH WILAYAH JAKARTA - Andini Larashati, Setya
Geographically, the study area is located in UTM coordinates of 686589 mE – 718321 mE and 9295418 mN – 9326737 mN with the total area of approximately 661.5 km2. The research area covers the whole area of Jakarta. Increase of population makes the consumption of groundwater of good quality in Jakarta increases. The study aims to analyze the distribution of groundwater types and determine the cause of the presence of salt water in the northern part based on 250 groundwater samples in Aquifers 1 and 2. The parameters analyzed were total dissolved solids (TDS), major ions, and elevation of Groundwater Level (GL). Aquifers 1 and 2 in the study area are composed of sandstone with clay intercalation that belongs to Citalang and Middle Kaliwangu Formations. All groundwater sample data were processed using Piper Diagrams and interpreted using Surfer application in the form of groundwater type distribution, TDS, and groundwater flow maps. Further analysis shows that Aquifers 1 and 2 are dominated by bicarbonate anions and sodium cations. In general, the southern part of the study area is dominated by groundwater type of Ca(HCO3)2, the middle part was dominated by non-dominant groundwater type and NaHCO3, and the northern part of the study area was dominated by groundwater type of NaCl. In general, the direction of groundwater flow in Aquifers 1 and 2 are south-north. The presence of saltwater in the northern part is interpreted as not caused by sea water intrusion. In Aquifer 1, saltwater is interpreted as rainwater which contains NaCl, and evaporation. In Aquifer 2, saltwater is interpreted as the influence of connate water.